Theodore Roosevelt and the international rivalries - Esthus, Raymond A. (Waltham, Mass. Ginn-Blaisdell, 1970)
"During an era of isolationist sentiment in America, Theodore Roosevelt employed secret diplomacy to placate rivalries without involving his country in commitments abroad. Unlike later presidents who were thrust into international politics by circumstances directly affecting the security of the United States, Theodore Roosevelt voluntarily plunged into the center of power struggles"--From publisher description.
Introduction -- 1. Roosevelt and the diplomats -- 2. The balance of power in East Asia -- 3. Britain versus Germany, 1901-1905 -- 4. The Moroccan crisis -- 5. The Algeciras Conference -- 6. Britain versus Germany, 1906-1909 -- 7. Rivalries in East Asia.
Donations in memory of Loinel V. Patenaude.
Included in the Dean Bonifacio Salamanca Collection.
Bibliography: p. 151-157.
Keywords: Roosevelt, Theodore -- 1858-1919.; United States -- Foreign relations -- 1901-1909.